Studies on Structures and Functions of Kinases leading to Prostate Cancer and Their Inhibitors - Nagappa, Anantha N.; Bhatt, Shvetank; Kanoujia, Jovita (Current Enzyme Inhibition, 2020)
Background: Cancer is the uncontrolled growth of abnormal cells in any part of the body. These abnormalities in the cells make them cancer cells, malignant cells, or tumour cells. These cells can infiltrate normal body tissues. Prostate Cancer begins when cells in the prostate gland start to grow out of control. Introduction: According to the National Cancer Institute, an estimated 20 percent of men experience Prostate Cancer in their lifetimes. Prostate Cancer can be divided into castration sensitive or hormone- sensitive Prostate Cancer (CSPC or HSPC) and castration-resistant Prostate Cancer (CRPC). Different therapies showed potential for the treatment of Prostate Cancer in that androgen receptor antagonist, cytochrome p17 inhibitors, radiation therapy, brachytherapy, surgical removal of the gland, androgen deprivation therapy and LnRH antagonists are some of the important ones. Despite various available treatment options in our understanding of the biological basis of Prostate Cancer, the management of the disease, especially in the castration-resistant phase, remains a significant challenge. Several Tyrosine kinase inhibitors (TKIs) have been evaluated in the preclinical setting in Advanced Prostate Cancer. TKIs are small drug molecules that work by competitive ATP inhibition at the catalytic binding site of tyrosine kinase. This results in complete inhibition of the catalytic activity of certain enzymes. If chosen correctly, TKIs can target and inhibit critical, mutated pathways important for the development, progression and metastasis of Prostate Cancer. The review focuses on various tyrosine kinase drug targets and their chemical structure to discuss the mechanism and pathways in the treatment of Prostate Cancer. Methods: The method adopted for the study was mainly based on the secondary search through a systematic literature review. Targets discussed in this review include the epidermal growth factor family (EGFR), vascular endothelial growth factor family (VEGF) receptor, c-Src family kinases (Proto-oncogene tyrosine-protein kinase) (c-Src), platelet-derived growth factor (PDGF) and cmesenchymal- epithelial transition factor (c-Met), which showed some promising results in various studies. Results: Even with the strong scientific rationale for many TKIs in the treatment of Prostate Cancer, the clinical trial experience showed some negative results in advanced phases. However, despite various challenges, the validation studies targeting kinases hold great potential in Prostate Cancer. Given the success of kinase inhibitors across multiple other cancer types, it is likely that this drug class will eventually improve outcomes in Prostate Cancer. Conclusion: Modifications in structures and certain other aspects of TKIs may make these agents promising for the treatment of Prostate Cancer.
Keywords: lapatinib